Axiology of Independent Curriculum as Orientation for Developing Islamic Religious Education (PAI) at MAN 2 Bima City - Akbar, Muhammad; Tang, Muhammad; Mappatunru, Sakkirang (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2025)
This study aims to examine the axiology of the Independent Curriculum as an orientation for the development of Islamic Religious Education (PAI) at MAN 2 Kota Bima. The Independent Curriculum offers a flexible learning approach that focuses on strengthening character, so it has great potential in strengthening the relevance of Islamic religious education in madrasahs. With a qualitative approach and case study design, this study involved the head of the madrasah, PAI teachers, and students as participants. Data collection techniques were carried out through in-depth interviews, participatory observation, and documentation. The results of the study indicate that the implementation of the Independent Curriculum at MAN 2 Kota Bima contributed significantly to the formation of student character through the integration of spiritual, moral, and social values ​​in PAI learning. From an axiological perspective, the values ​​of honesty, discipline, and tolerance are important foundations that are instilled contextually. However, challenges remain, such as limited human resources, lack of intensive training for teachers, and the need to adapt to changes in the learning paradigm. These findings emphasize the importance of strengthening the capacity of educators and systemic support so that the Independent Curriculum truly functions as a vehicle for fostering students' religious and social character holistically. This research is expected to provide academic and practical contributions in the development of a more transformative Islamic religious education curriculum in various madrasas in Indonesia.